Perceptions of Ride Hailing for First Mile and Last Mile Trips in Yogyakarta Urban Area - Vemantyasto, Turas Nur; Irawan, Muhammad Zudhy; Malkhamah, Siti (Universitas Negeri Yogyakarta, 2024)
The high population density and mobility in the Yogyakarta Urban Area necessitate the improvement of transportation services. The current population density in Yogyakarta is approximately 13,007 people per square kilometer, and the city experiences significant daily commuter traffic. Problems occur because the available modes of transportation have several limitations. While the existence of stations/airports/terminals requires connectivity from other modes of transportation. Ride-hailing services have emerged as a convenient and practical solution for users. However, the integration of ride-hailing services with multimodal systems, particularly for first mile and last mile trips, is still considered inadequate, and there is limited empirical evidence on this matter. Therefore, conducting an in-depth study is crucial to comprehend users' perceptions of ride-hailing for first mile and last mile trips. Primary data collection was conducted by face-to-face and online using Google Form on 416 respondents. The primary data collection technique was carried out using the convenience sampling method. The data collected consists of socio-demographic data, travel characteristics and variables that influence respondents to use ride-hailing for first mile and last mile trips. This research uses descriptive analysis, and exploratory factor analysis, by employing exploratory factor analysis, the results reveal that there are 2 factors that influence respondents to choose to use ride-hailing, namely convenience and practicality and service performance. Convenience and practicality refer to the ease of service, including payment and ordering, and the ability for ride-hailing services to pick up or drop off users at home. Service performance includes short waiting times, certain travel times, comfort, and safety. Improving these aspects could enhance the integration of ride-hailing services with existing transportation systems, addressing current inadequacies.